2015
DOI: 10.1002/lt.24060
|View full text |Cite
|
Sign up to set email alerts
|

Preexisting atrial fibrillation and cardiac complications after liver transplantation

Abstract: Atrial fibrillation (AF) is the most common cardiac arrhythmia, and it is associated with increased cardiovascular morbidity and all-cause mortality. Our aim was to determine the impact of preexisting AF on patients undergoing liver transplantation (LT). A retrospective case-control study was performed. Records from patients who underwent LT between January 2005 and December 2008 at Mayo Clinic Florida were reviewed. Patients with preexisting AF were identified and matched to patients who did not have a diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 31 publications
1
47
0
Order By: Relevance
“…Atrial fibrillation is the most common cardiac arrhythmia with prevalence estimates ranging from 0.95% to 2.3% in the general population(30) and AF significantly increases cardiovascular and cerebrovascular morbidity, as well as all-cause mortality(31). In a recent single-center study, the prevalence of AF among LT recipients was reported at 4.5% and patients with AF had a higher incidence of intraoperative cardiac events and a higher cardiovascular morbidity rate though there was no impact of AF on overall graft or patient survival(17). Thus, AF may be a marker of risk for future decompensation and should be considered as part of the risk profile in candidate selection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atrial fibrillation is the most common cardiac arrhythmia with prevalence estimates ranging from 0.95% to 2.3% in the general population(30) and AF significantly increases cardiovascular and cerebrovascular morbidity, as well as all-cause mortality(31). In a recent single-center study, the prevalence of AF among LT recipients was reported at 4.5% and patients with AF had a higher incidence of intraoperative cardiac events and a higher cardiovascular morbidity rate though there was no impact of AF on overall graft or patient survival(17). Thus, AF may be a marker of risk for future decompensation and should be considered as part of the risk profile in candidate selection.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, little is known about the impact of non-coronary heart disease, including arrhythmia, heart failure and stroke, on LT outcomes. In one small single center study, preexisting atrial fibrillation (AF) was shown to increase risk of intraoperative cardiac events and cardiovascular morbidity after LT(17), and among the general population AF is associated with an increased risk of stroke, heart failure, and all-cause mortality representing a substantial healthcare burden with high rates of re-hospitalization and healthcare utilization(20). Utilizing data from the Organ Procurement and Transplantation Network (OPTN) we recently demonstrated that CVD in general has surpassed infection and graft failure as the leading cause of early mortality in the United States, accounting for over 40% of deaths within 30 days of LT(1).…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Patients with pre-existing AF have increased intraoperative and postoperative cardiovascular complications, graft dysfunction and mortality. 3,105 AF identified during pre-LT evaluation should prompt investigation for other cardiac pathology. Symptomatic patients or those with uncontrolled ventricular response may benefit from a cardiology consultant for management recommendations.…”
Section: Cardiac Dysrythmiasmentioning
confidence: 99%
“…It has been suggested that AF is associated with worsened outcomes in the perioperative period and immediate postoperative period in patients undergoing LT 21, 22. Given the findings of this study, AF is likely a marker of illness severity rather than a major cause of poor outcomes.…”
Section: Discussionmentioning
confidence: 62%